Pancreatoduodenectomy with or without prophylactic falciform ligament wrap around the hepatic artery for prevention of postpancreatectomy haemorrhage: randomized clinical trial (PANDA trial). Issue 1 (8th November 2021) - Welsch, Thilo; Müssle, Benjamin; Korn, Sandra; Sturm, Dorothée; Bork, Ulrich; Distler, Marius; Grählert, Xina; Klimova, Anna; Trebesius, Nicole; Kleespies, Axel; Kees, Stefan; Beckert, Stefan; et al.
Abstract: Background: Postpancreatectomy haemorrhage (PPH) is a rare but potentially fatal complication after pancreatoduodenectomy. Preventive strategies are lacking with scarce data for support. The aim of this study was to investigate whether a prophylactic falciform ligament wrap around the hepatic and gastroduodenal artery can prevent PPH from these vessels. Methods: In a randomized, controlled, multicentre trial, patients who were scheduled for elective open partial pancreatoduodenectomy with pancreatojejunostomy between 5 November 2015 and 2 April 2020 were randomly allocated in a 1 : 1 ratio to undergo pancreatoduodenectomy with (intervention) or without (control) a falciform ligament wrap around the hepatic artery. The primary endpoint was the rate of clinically relevant PPH from the hepatic artery or gastroduodenal artery stump within 3 months after pancreatoduodenectomy. Secondary endpoints were the rates of associated postoperative complications, for example postoperative pancreatic fistula (POPF) and PPH. Results: Altogether, 445 patients were randomized with 222 and 223 in each group. Among the patients included in modified intention-to-treat analysis (207 in the intervention group and 210 in the control group), the primary endpoint was observed in six of 207 in the intervention group compared with 15 of 210 in the control group (2.9 versus 7.1 per cent respectively; odds ratio 0.39 (95 per cent c.i. 0.15 to 1.02); P = 0.071). Per protocol analysis showed a significant reduction in the intervention group (odds ratio 0.26 (95 per cent c.i. 0.09 to 0.80); P = 0.017). A soft pancreas texture (43 per cent) and the rate of a clinically relevant POPF were evenly (20 per cent) distributed between the groups. The rate of any clinically relevant PPH including the primary endpoint and other bleeding sites was not significantly different between intervention and control groups (9.7 versus 14.8 per cent respectively). Conclusion: A falciform ligament wrap may reduce PPH from the hepatic artery or gastroduodenal artery stump and should be considered during pancreatoduodenectomy. Registration number: NCT02588066 (http://www.clinicaltrials.gov ). Abstract : The randomized multicentre clinical trial analysed if a falciform ligament wrap around the hepatic artery (HA) including the gastroduodenal artery stump (GDA) during pancreatoduodenectomy lowers the rate of postoperative bleeding from the HA or GDA. Some 400 patients were randomized into two parallel groups. The borderline significant results indicate that a falciform ligament wrap may be effective to reduce the rate of haemorrhage from the HA/GDA by approximately 5 per cent.